Eshtablishment of "BRAC Onnesha" nano sattelite ground station and comparative analysis of different types of antenna as a portable low earth orbit sattelite ground station receiving antenna - Haque, Md. Arafat; Arifin, Jamil (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.